Effect of Milling Time and PCA on Electrode Properties of Cu2O-ZnO/C Catalyst Alloy used on Electrochemical Reduction Method of CO2 - Rohendi, Dedi; Syarif, Nirwan; Rachmat, Addy; Mersitarini, Dewi; Ardiyanta, Dimas; H. Erliana, Whiny; Mahendra, Isya; Febrika S., Nyimas; Yulianti, Dwi Hawa; Amelia, Icha; Reo, Muhammad Al Reka (International Journal of Integrated Engineering, 2022)
Carbon dioxide is one of the greenhouse gases that cause climate change, thus the effort for reducing the concentration of CO2 is necessary, for example through the conversion of CO2. The conversion of CO2 into methanol plays an important role because, in addition to reducing greenhouse gas, it is also creating a future energy carrier needed in fuel cell technology. One of the CO2 conversion methods is the electrolysis method using MEA. The electrochemical CO2 conversion in this study used a Cu2O-ZnO/C composite catalyst made by milling methods at various milling times, as well as the effect of PCA utilization. The catalysts were characterized using Particle Size Distribution (PSA), Brunauer-Emmett-Teller (BET), Cyclic Voltammetry (CV), Electrochemical Impedance Spectroscopy (EIS), and SEM-EDX analysis. The results of PSA and BET characterization showed that the longer the milling time, the smaller the particle size and the higher the relative surface area. The use of PCA increased the unoxidized Cu content as indicated by the SEM-EDX results. Based on the results of CV analysis, the catalyst that has the largest ECSA (Electrochemical surface area) value is the catalyst milled using PCA and the milling time is three hours.